REGENERATION POTENTIAL AND MAJOR METABOLITE ANALYSIS IN NOOTROPIC PLANT-BACOPA MONNIERI (L.) PENNELL - T G, Umesh; Sharma, Ashwani; N Rao, Nagashree (Asian Journal of Pharmaceutical and Clinical Research, 2014)
OBJECTIVE: Bacopa monnieri (L) Pennell, commonly known in India as ‘Brahmi' is an important nootropic plant. The study was mainly aimed at the mass multiplication of B. monneri and the effect of various growth regulator regimes for their active principle accumulation in regenerated plants. METHOD: In this study, a protocol to produce high frequency of in vitro cultured multiple shoots / plantlets were established both by direct and callus based indirect regeneration using leaf and nodal explants. In direct regeneration, a single leaf grown on MS basal plant medium supplemented with 2mg/L kinetin gave large number of multiple plantlets. On the other hand the callus based regeneration using leaf as explant grown on MS basal plant medium supplemented with 1mg/L Benzyl aminopurine (BAP) and 0.5mg/L IAA produced large number of side shoots / multiple plantlets. The successfully acclimatized plants were screened for major metabolites /active principles using HPLC. RESULT: Influence of Cytokinins and supplementation with auxins for the production of multiple shoots was investigated . 2mg/L kinetin alone showed highest number of shoots whereas the combination of Kin / BAP or Kin / IAA showed less number of shoots. Bacopaside content of regenerated shoots varied with hormonal treatments. CONCLUSION: This study will facilitate the mass propagation and transformation of this nootropic plant. In addition the study can be used for commercial production of secondary metabolites like Bacopaside using different hormone combinations for elicitation. Key words: Secondary metabolites, Bacopasides, plant tissue culture, multiple shoots